Comparison of Outcomes Between Open Major Hepatectomy Using CUSA and Laparoscopic Major Hepatectomy Using “Lotus” Liver Blade. A Propensity Score Matched Analysis - Baltatzis, Minas; Mirza, Ahmed; Stathakis, Panos; Tyurkylmaz, Ahmed; Jamdar, Saurabh; Siriwardena, Ajith K.; Sheen, Aali J. (Frontiers in Surgery, 2019)
Introduction Evolution in laparoscopic liver surgery during the past two decades is an indisputable fact. According to the second international consensus conference for laparoscopic liver resection held in Morioka, Japan in 2014 major resections are still regarded as innovative procedures in the exploration phase. On this basis, our study aims to explore the efficacy and safety of laparoscopic versus open major liver resection and therefore increase the existing evidence on major laparoscopic liver surgery. Methods All consecutive patients who underwent major liver resection, open and laparoscopic from January 2016 to May 2018 were identified from our prospectively maintained database. Propensity score matching analysis was performed using R statistical tool in SPSS to isolate matched open and laparoscopic cases which were compared for intraoperative and postoperative short-term outcomes. Lotus ultrasonic energy device was used for parenchymal transection in laparoscopic cases versus CUSA in open procedures. Results Propensity score matching analysis was performed on 82 consecutive patients (61 open and 21 laparoscopic major hepatectomies) resulting in 40 matched patients, 20 in each group. The mean total duration of surgery and duration of parenchymal transection were slightly longer in the laparoscopic group (p=0.419, p=0.348). There was no difference in the intraoperative and postoperative transfusion rates. Patients after laparoscopic surgery were discharged 2 days earlier on average (p=0.310). No difference was observed in complication rates and mortality. Conclusion Our data did not reveal inferiority of the laparoscopic major hepatectomy versus the open approach in any parameter compared. The use of the Lotus ultrasonic energy device appeared to be efficient and safe for parenchymal transection in the laparoscopic procedures.